Daya Terima Dan Kandungan Serat Pangan Snack Bar “SANGTUL” Sebagai Pangan Fungsional Sumber Prebiotik - Sunarto Sunarto; Hendrayati Hendrayati; Nur Fajriany Anwar (Media Kesehatan Politeknik Makassar, 2023)
Dietary fiber has the benefit of being a good source of prebiotics to maintain the health of the digestive tract. Kepok bananas contain inulin and fructooligosaccharides which are considered food for the intestinal microflora. Rice bran contains insoluble food fiber which can work as a source of prebiotics. This study aims to determine the acceptability and fiber content of the "SANGTUL" snack bar, namely banana kepok flour and rice bran flour as functional food sources of prebiotics. The research method is a pre-experimental design with a Post Test Group Design. Acceptability was assessed based on the hedonic test by 30 panelists and analysis of dietary fiber content using the gravimetric method with 2 repetitions. The results showed that the acceptability of the snack bar "SANGTUL" banana flour kepok substitution of rice bran flour from the most preferred color aspects, namely all concentrations, aroma concentration aspects (90%:10%), texture aspects concentration (90%:10%), and aspect of taste concentration (90%: 10%) so that the average acceptance of the most preferred snack bar is the concentration of kepok banana flour substitution of rice bran flour (90%: 10%). The results of the food fiber content of the snack bar "SANGTUL" banana kepok flour substituted for bran flour with a concentration (90%:10%) of 11.42 g per 100 g snack bar. It is suggested that in the manufacture of banana flour kepok snack bar substitution of rice bran flour in further research, test the content of other nutrients.